2005
DOI: 10.1103/physrevlett.95.085002
|View full text |Cite
|
Sign up to set email alerts
|

Ab-Initio Simulations of the Optical Properties of Warm Dense Gold

Abstract: Using a combination of classical and ab-initio molecular dynamics simulations, we calculate the structure and the electrical conductivity of warm dense gold during the first picoseconds after a short-pulse laser illumination. We find that the ions remain in their initial fcc structure for several picoseconds, despite electron temperatures ranging from a few to several eV after the laser illumination. The electrical conductivities calculated under these nonequilibrium conditions and using the latter assumption … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
50
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(60 citation statements)
references
References 16 publications
10
50
0
Order By: Relevance
“…4). We have performed similar calculations for tantalum, another approximately half-filled d-band transition bcc metal, and found that Ta exhibits the same kind of behavior as a function of T e as W. On the other hand, previous calculations for Au have shown that Au undergoes phonon hardening as the electronic temperature increases [50], if the unit cell volume is kept at V eq (300 K), FIG. 4.…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations
“…4). We have performed similar calculations for tantalum, another approximately half-filled d-band transition bcc metal, and found that Ta exhibits the same kind of behavior as a function of T e as W. On the other hand, previous calculations for Au have shown that Au undergoes phonon hardening as the electronic temperature increases [50], if the unit cell volume is kept at V eq (300 K), FIG. 4.…”
Section: Discussionmentioning
confidence: 89%
“…We note that different structural transformations have been proposed caused by a soft mode on the -N line of the bcc Brillouin zone [54,56,57], particularly bcc-to-fcc and bcc-to-hcp transformations caused by the ,0]. We would like to emphasize that these transformations are totally different from the nonthermal melting of silicon, where phonon softening is observed in the whole Brillouin zone [50].…”
Section: Phonon Spectrum Calculationsmentioning
confidence: 98%
See 2 more Smart Citations
“…The study of the optical properties is possible both using modern picosecond diagnostics 1,2 and computational methods 1,7 .…”
Section: Introductionmentioning
confidence: 99%